ANALISIS KAUSALITAS INFRASTRUKTUR TRANSPORTASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Didi Nuryadin; Aretha Dhea Anjani (Develop, 2023)
This research aims to analyze the causality between transportation infrastructure and economic growth in Indonesia using Vector Error Correction Model (VECM) with data from 1990-2020. The results show that there is a two-way causality between road and air transportation infrastructure and economic growth. Additionally, there is also a two-way causality between economic growth and gross fixed capital formation with road and air transportation infrastructure. The findings indicate that road transportation infrastructure, air transportation, and gross fixed capital formation have a significant influence on economic growth in both the short and long term. Furthermore, air transportation infrastructure, road transportation infrastructure, and economic growth also have a significant influence on gross fixed capital formation in both the short and long term. This research also found that economic growth and gross fixed capital formation have a significant influence on road and air transportation infrastructure. Therefore, these results can provide input for the government in determining transportation infrastructure development policies that can support economic growth and gross fixed capital formation in Indonesia.